(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
The Project by Ludovico Quaroni for the Opera House in Rome (1983)thrusts his conception within his ancient project of the Piazza Imperiale for E42 (with Saverio Muratori and Francesco Fariello, 1937), using the elongated proportions and small intercolumniation typical of the Eastern Hellenistic phase of architecture. Reasoning with the drawing, as Vincenzo Fasolo taught us to, with ancient monuments. Â